A comprehensive immune repertoire study for patients with pulmonary tuberculosis. Issue 7 (7th June 2019) - Fu, Yingyun; Li, Bo; Li, Yazhen; Wang, Minlian; Yue, Yongjian; Xu, Lan; Li, Shulin; Huang, Qijun; Liu, Song; Dai, Yong
Abstract: Background: Tuberculosis (TB) is a major global health problem and has replaced HIV as the leading cause of death from a single infectious agent. Methods: Here, we applied high throughput sequencing to study the immune repertoire of nine pulmonary tuberculosis patients and nine healthy control samples. Results: Tuberculosis patients and healthy controls displayed significantly different high express clones and distinguishable sharing of CDR3 sequences. The TRBV and TRBJ gene usage showed higher expression clones in patients than in controls and we also found specific high express TRBV and TRBJ gene clones in different groups. In addition, six highly expressed TRBV/TRBJ combinations were detected in the CD4 group, 21 in the CD8 group and 32 in the tissue group. Conclusion: In conclusion, we studied the patients with tuberculosis as well as healthy control individuals in order to understand the characteristics of immune repertoire. Sharing of CDR3 sequences and differential expression of genes was found among the patients with tuberculosis which could be used for the development of potential vaccine and targets treatment. Abstract : Tuberculosis patients and healthy controls displayed significantly different high express clones and distinguishable sharing of CDR3 sequences. The TRBV and TRBJ gene usage showed higher expression clones in patients than in controls and we also found specific high express TRBV and TRBJ gene clones in different groups. In addition, six highly expressed TRBV/TRBJ combinations were detected in the CD4 group, 21 in the CD8 group and 32 in the tissue group.